Pursuit of excellence by Muslim scientists with a special reference to Ibn Sina / Mohd Hishamuddin A Hamid - Mohd Hishamuddin, A Hamid (2011)
This dissertation has the objective of studying the pursuit of excellence by Muslim Scientists during the height of Islamic Civilization with a special reference to Ibn Sina. It is hope that through this study we can obtain some information or guidelines which can be used and emulated by present day scientists to achieve the excellence that the Muslims Scientists of that time had attained. Why do we need to achieve that level of excellence? The present day predicament of the Muslim Ummah where we are ostracized, discriminated and looked down upon by friends and foes alike. We have to redeem ourselves in the eyes of the world and especially in the eyes of Allah AlMighty that we are the best Ummah and Islam is the highest way of life and be worthy of the blessing of Islam. The excellence of the Muslim scholars and scientists of yesteryears has to be recapitulated. Why Ibn sina? Ibn Sina is the most famous Muslim scholar of the Islamic civilization and some even cited him as the most excellent with his wide ranging work from medicine, astronomy, philosophy, language, politics and many other various fields. His work and life had been documented and studied since his time until the present time. In this study the author presented the criteria for excellence and put forward the hypothesis of Iman as the special criteria that made the difference between the Muslims and the non-Muslims. The excellence and contributions of Muslim scientists during the height of Islamic civilization between the 7th-14th Ibn Sina’s life from the influence of his parents, his earliest education and his surroundings seems to have molded his character into a dedicated and resilient scholar. He was exposed to knowledge and intellectual discussion various fields at an early age and became a competent practitioner of medicine by the age of 18. Ibn Sina had many special characteristics which can be emulated by later scholars. His dedication, his confidence, his resilience despite the hostile and rough conditions he had to endure, his power of concentration being able to work continuously for hours sometimes under difficult circumstances. Ibn Sina’s work on medicine and philosophy were and until today the most respected and most studied. His Canon of Medicine were used as the primary text for the study of medicine with some institutions in Europe using it even until the 19th century. Ibn Sina from the facts presented was a person with Iman and his early education in religious studies and able to memorize the whole of the Al Quran had made him the renowned scholar that he is although with many eccentricities. centuries were incomparable and undisputed as compared civilizations. This period produced many distinguished Muslim scholars in many varying fields of studies and their work were the basis of the development of western science. Some scholars attributed the advent of western science from the findings and works of Muslim scientists without which western science will not have achieved or attained the present dominance and prominence. The Ummah to recap the excellence of yesteryears, they have to study their history, the sirah of the Prophet Mohamad SAW, the earlier Quranic generation of the sahabahs, the tabiin and the scholars. Many of their efforts and practices that made them knowledgeable and respected had not been sustained thus resulting in the mundane and oppressed Ummah of the period after the 14th century until present. The factors which brought Islamic Civilization to the height of its glory were scrutinized and also that which brought the decline in order to find the remedies. In conclusion the Ummah was blessed with excellence and glory when they have Iman and practiced Islam as a way of life. The lessons from the period of glory of the Islamic Civilization have to be learnt and emulated and pray and be confident that Islam will bring again the glory in this world and the hereafter.